The sound of sleighbells - Dailey, Janet (Kensington Publishing Corp., 2023)
When fate brings the man she once loved together with the son he never knew he had, Ruth McCoy knows it is only a matter of time before Judd Rankin learns the truth and wonders if the revelation will shatter the tender feelings between them, or be her family's greatest gift.
Keywords: Man-woman relationships -- Fiction; Divorced women -- Fiction; Single mothers -- Fiction; Ranchers -- Fiction; Texas -- Fiction; Christmas fiction; Romance fiction; Novels